PENYULUHAN KESEHATAN TENTANG MANFAAT KONSUMSI TABLET ZAT BESI PADA IBU HAMIL DI TPMB Bd. BOINEM, S.ST - Boinem, Boinem; Oktaviani, Rizki; Fitriani, Alifia; Handayani, Yuni (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2024)
Iron deficiency anemia in pregnant women can affect the growth and development of the fetus or baby during pregnancy and afterward. Providing iron tablets is one of the most effective strategies for preventing and controlling nutritional anemia in increasing hemoglobin levels in pregnant women. Consuming iron tablets in pregnant women is very important in meeting the nutritional needs of the fetus, preventing anemia in pregnant women, reducing the risk of death in mothers due to postpartum hemorrhage. The aim of this community service activity is to increase awareness and compliance regarding the importance of consuming iron tablets. The target of this activity is all pregnant women in TPMB Bd. Boinem, S.ST. The media used was a leaflet containing information about the importance of iron tablets. The method used is lecture and discussion, in the initial stage before the extension a pretest is carried out by providing a chair, then at the end of the question and answer session it is followed by a posttest as an evaluation of the results of the extension.